2011 Triennial Surveillance Review : Report of the External Advisory Group. (Policy Papers; Policy Paper, 2011)
This report was prepared by the External Advisory Group (EAG) for the 2011 Triennial Surveillance Review (TSR). The Group comprised the following members: Shankar Acharya, Marc Antoine Autheman, Kemal Dervis, Martin Hellwig, Takatoshi Ito, David Li, Pedro Malan, Stephen Pickford, Chukwuma Charles Soludo, Umayya Toukan, and Edwin Truman. The EAG was set up to provide an independent check on staff's analysis and recommendations which are set out in the 2011 Triennial Surveillance Review-Overview Paper. The EAG contributed in written form and met twice during the course of the Triennial Surveillance Review (TSR)-on April 18 and July 29, 2011-to discuss the direction, emerging findings, and recommendations of the review.